ENHANCING STUDENT CREATIVITY IN CNC COURSES THROUGH MARKETPLACE-BASED TEACHING FACTORY: A CLASSROOM ACTION RESEARCH - Wirawan Sumbodo; Kriswanto; Cahyanto, Septian Eko (Jurnal Pendidikan Teknik Mesin, 2025)
The rapid transformation brought by Industry 4.0 and Society 5.0 demands vocational education to produce graduates who are not only technically competent but also creative and entrepreneurial. This study aims to enhance student creativity in CNC (Computerized Numerical Control) learning by implementing a marketplace-based Teaching Factory model. Using a Classroom Action Research (CAR) design, the study involved 20 students of the Mechanical Engineering Education Program over two learning cycles. Each cycle included planning, implementation, observation, and reflection stages. The results showed significant improvements across four assessed aspects: technical skills (from 74.1 to 86.6), product design (from 75.1 to 87.9), marketing (from 73.5 to 86.5), and reflective learning (from 78.2 to 91.0). The marketing aspect experienced the highest gain, indicating that digital marketplaces provide an effective platform for practical entrepreneurial learning. This study concludes that integrating marketplace platforms into Teaching Factory learning can significantly foster creativity and entrepreneurial skills in vocational students.